Some Lower Cretaceous brachiopods from East Greenland - Owen, E. F. (Meddelelser om Grønland, 1976)
The paper includes a brief description of brachiopods collected from two contemporaneous localities in East Greenland which appear to represent different facies. One brachiopod assemblage from Wollaston Forland shows distinct affinities to boreal Valanginian genera and species previously described from north Germany and northern England, while the other assemblage, from Traill Ø, shows a remarkable similarity to the very distinctive Tethyan fauna of middle European "Alpine" facies containing Pygope and Lacunosella spp.